SOME ASPECTS OF AVIATION SERVICE MARKET - A. V. Parkhimovich (Научный вестник МГТУ ГА, 2018)
The present day globalization in economy is closely connected with the development of air transport-one of the fastest growing sectors of economy, which provides long-distance transport, primarily to passengers. The mobility of population has increased and as a consequence the single transport space has been formed. After the crisis of 2015–2016 the economy of civil aviation is characterized by the rapid growth, increased passenger turnover, a high percentage of seat occupancy and the change in the structure of the air transportation market. The state of the air transportation market is characterized by globalization, deregulation, information and privatization. The services which air companies offer to the market are related to a high-tech product. At the same time, modern conditions require airlines to take measures to improve their performance, taking into account the internal and external factors affecting this business, as well as a set of incentive measures for workers in this industry. Thus, the article discusses the process of industry deregulation, gives several examples of market functioning models, highlights their main characteristics and shows options for making managerial decisions. Efficiency evaluation is a prerequisite condition for the implementation of airline development strategies. The principles of market economy required the restructuring of relations in distributive system and material incentive. In this regard, we summarize the experience of several labor remuneration decisions, as an integral part of airline management. The article gives an overview of the modern air transportation market characteristics, identifies the problems and prospects for its development. The relevance of the article is stipulated by the expanded presence of airlines in the world market and, as a consequence, by the necessity to investigate the up-to-date trends in market development, exposure the main factors that affect the competitiveness of air companies. The article is of interest for aviation experts as well as for readers who are keen on aircraft.